Debt Maturity and the Effects of Growth Opportunities and Liquidity Risk on Leverage - Johnson, S. A. (Review of Financial Studies, 2002)
I test the hypothesis that short debt maturity attenuates the negative effect of growth opportunities on leverage. Using simultaneous equations with leverage and maturity endogenous, I find strong support for an economically significant attenuation effect. The negative effect of growth opportunities on leverage for firms with all shorter-term debt is less than one-sixth as large as the effect for firms with all longer-term debt. Short maturity also increases liquidity risk, however, which negatively affects leverage. The results suggest that firms trade off the cost of underinvestment problems against the cost of liquidity risk when choosing short maturity.